Organic Feed Enrichment Effects toward Growth Performance and Egg Production of Oithona similis - Diana Chilmawati; Johannes Hutabarat; Sutrisno Anggoro; Suminto Suminto (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
The optimum condition of culture media and feed diets which fit the necessities of Oithona similis life (ecophysiological) is very important for it to grow and develop in its maximum. The enrichment of O. similis feed can be done by adding fermented organic feed. Providing organic feed with optimum protein content is necessary to support the growth process and reproduction of O. similis. Osmoregulation process of water organism which is influenced by media salinity is related to bioenergetics process as the effort to use feed energy for the growth. This research aimed to examine the effect of different organic feed protein content and to determine the optimum point which may result in the best growth and egg production of O. similis in the optimum condition of culture media. The study used an experimental method with a completely random design consisting of 4 treatments and 4 repetitions each, i.e. O. similis culture with A. 25%; B. 30%; C. 35%; and D. 40% organic feed protein content. The results showed that the difference of protein content in organic feed affects the growth and production of O. similis eggs. The optimum point of protein content in the fermented organic feed is on protein content B, i.e. 30%, which resulted in the best growth performance (70.44 ± 0.43 ind.mL-1 total density, 0.213 ± 0.001.day-1 population growth rate, and 27.38 ± 0.48 eggs.ind-1 egg production. (ttujuan dan pembahasan harus past tense), Tujuan di abstrak minimal harus menggambarkan atau sama denga tujuan di pendahuluan)Keywords: enrichment, Oithona similis, organic feed, protein, reproduction